Water Absorption and Mechanical Behavior of Hybrid Reinforced Epoxy LY556 Composites: Experimental Analysis - Rania Saadeh; Nabil Talbi; Sami Znaidia; Ahmad Qazza; Ghassan Abufoudeh; Mohamed Kezzar; Ibrahim Mahariq; Mohamed Rafik Sari (Journal of Natural Fibers)
This study investigates for the first time the effects of reinforcing epoxy composites with Jute, Filass. A, and Filass. B fibers (JFs, FAFs, FBFs) on mechanical and morphological properties, including tensile, flexural, and impact strength, void content, and water absorption. The hybrid composites were fabricated using compression molding techniques with different fiber volume fractions. Scanning Electron Microscopy (SEM) analysis was conducted to examine the bonding behavior and internal structure of the fractured surfaces. Mechanical characterization through tensile testing demonstrated that the inclusion of these fibers enhanced the composite’s mechanical performance. Specifically, hybrid composites such as (JFs/FAFs), (FAFs/FBFs), (JFs/FBFs), and (JFs/FAFs/FBFs) displayed improved tensile strength, with the (JFs/FAFs/FBFs) combination achieving the highest tensile value of 19.08 MPa and highest impact value of 18.99 J. Additionally, increasing the fiber content led to higher water absorption and thickness swelling, with the (JFs/FAFs/FBFs) composite showing the greatest values. Overall, the study concludes that hybridization improves the mechanical properties, especially flexural performance, of epoxy-based composites.